Novel Measures for Thermal Management of Silicon Photonic Optical Phased Arrays - Pedro Andrei Krochin Yepez; Ulrike Scholz; Jan Niklas Caspers; Andre Zimmermann (IEEE Photonics Journal, 2019)
Silicon photonics has become a promising technology for fabrication of compact, highly integrated systems. When dealing with phase sensitive silicon photonic components, however, temperature control and in particular, reduction of temperature gradients across phase sensitive components becomes crucial. Solid-state optical beam steering using optical phased arrays (OPAs), is an exemplary system, which could be miniaturized by using silicon photonics and where temperature control is of utmost importance. In order to reduce the system cost and size as well as to increase the steering velocity, it is desired to replace mechanical beam steering systems by solid-state steering systems. Due to their compatibility with CMOS fabrication processes, silicon photonics based OPAs are promising candidates to become the next generation beam steering solution. However, due to the large thermo-optic coefficient of silicon, these phased arrays are extremely sensitive to temperature. Thermal management of silicon-photonic based OPAs requires not only heat dissipation of integrated active components, but also reduction of temperature gradients across the phased array. Here a novel concept for thermal management of silicon photonic OPAs is proposed and analyzed using finite-element simulations. The proposed concepts show a formidable efficiency in improving the heat dissipation as well as in reducing temperature gradients across the array.